Does Media Education At Schools Develop Student´s Critical Competences? - Petranová, Dana (Communication Today, 2025)
Media education in formal education in Slovakia is the compulsory part of school curricula. One of the basic goals of media education is to teach pupils how to subject the media contents to critical analysis, in other words to develop their critical thinking abilities. The history of efﬁ ciency research and conﬁ rmation of the necessary inclusion of media education to schools does not have a long tradition. That was the reason for us to carry out the research and try to answer the question what is the relation between passing the course of media education and development of critical thinking competence. The study also offers information pointing to present-day limitations of formal media education in Slovakia; its ambition is to bring suggestions improving the current conditions.Media education in formal education in Slovakia is the compulsory part of school curricula. One of the basic goals of media education is to teach pupils how to subject the media contents to critical analysis, in other words to develop their critical thinking abilities. The history of efﬁ ciency research and conﬁ rmation of the necessary inclusion of media education to schools does not have a long tradition. That was the reason for us to carry out the research and try to answer the question what is the relation between passing the course of media education and development of critical thinking competence. The study also offers information pointing to present-day limitations of formal media education in Slovakia; its ambition is to bring suggestions improving the current conditions.